Electrophysiological Evaluation of the Facial Muscles in Congenital Unilateral Lower Lip Palsy. Issue 1 (January 2018) - Baba, Shintaro; Kondo, Kenji; Yamasoba, Tatsuya
Abstract : Objectives: Congenital unilateral lower lip palsy (CULLP) is a congenital facial asymmetry in which one corner of the mouth does not dip downward symmetrically (Kobayashi, 1979). We analyzed the electrophysiological findings in cases of CULLP to understand the facial nerve mechanisms underlying this pathological condition. Methods: The electrophysiological findings in 20 patients with CULLP including an electroneuronography (ENoG) of the orbicularis oris muscle, nerve excitability test (NET) results, and the blink reflex (BR) were analyzed. Results: Of 21 patients with CULLP, 20 underwent ENoG, 12 underwent a NET, and 14 underwent a BR examination. Nine of 19 patients with CULLP showed higher ENoG amplitude in the affected side than in the unaffected side. In four patients, the ENoG amplitude in the affected side was similar to that in the unaffected side whereas six patients had higher ENoG amplitude in the unaffected side. All patients showed a normal BR response and only one patient had a left–right difference in the NET response in the marginal mandibular branch. NET also demonstrated that the muscular twitch appeared on the lower lip of the affected side. Conclusion: These results suggested that in CULLP, each of the facial nerve branches including the marginal mandibular branch appeared to function within normal parameters. The marginal mandibular branch of the facial nerve, which usually innervates the depressor anguli oris and depressor labii inferioris muscles, may innervate adjacent muscles as well, such as the orbicularis oris muscle, during prenatal development.